2023
DOI: 10.1111/clr.14036
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontic outcomes of mandibular overdenture treatment with one or two implants: 4‐year results of a randomized clinical trial

Abstract: Objective: To assess the incidence of prosthodontic maintenance events and complications during 4 years of follow-up after mandibular overdenture treatment with one or two implants.Methods: Participants received one or two implants inserted in the midline (1-IOD group) or the lateral incisor-canine area bilaterally (2-IOD group). Implants were loaded with an early loading protocol after 3 weeks. Programmed recall visits were scheduled at the 6-, 12-, 36-, and 48-month follow-ups and nonprogrammed visits in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…These events were considered normal maintenance events in the short-term follow-up after overdenture treatment. This is in accordance with a previous RCT comparing the prosthodontic maintenance and complications of 1and 2-IODs over 4 years [24]. It was demonstrated that the majority of the aforementioned maintenance events occurred in the first year, irrespective of the treatment group, and that a longer follow-up did not increase the incidence of the events.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These events were considered normal maintenance events in the short-term follow-up after overdenture treatment. This is in accordance with a previous RCT comparing the prosthodontic maintenance and complications of 1and 2-IODs over 4 years [24]. It was demonstrated that the majority of the aforementioned maintenance events occurred in the first year, irrespective of the treatment group, and that a longer follow-up did not increase the incidence of the events.…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned previously, denture fracture has also been reported as a frequent complication associated with SIMOs [16,23,36,59]. Similar rates of this complication can be seen throughout various SIMO studies with no cast framework, with fractures occurring in 20 to over 30% of cases, and even increasing up to 55% in a long-term study [23,24,36,59]. Different distribution patterns of the incidence of denture fractures can be seen, some studies having an increase in the yearly incidence during follow-up, while in another, almost half of the denture fractures occurred during the first year [16,36].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The costs of overdentures retained by two implants are somewhat similar to those of conventional complete dentures. Using unsplinted anchors can lower the cost of implantretained overdentures compared to those with splinted anchors [14][15][16]. Even single implant overdentures can be efficient in improving patients' quality of life, as demonstrated by Abdelal et al [17].…”
Section: Introductionmentioning
confidence: 99%